Implementation and validation of a strongly coupled numerical model of a fully passive flapping foil turbine. (April 2021) - Duarte, Leandro; Dellinger, Guilhem; Dellinger, Nicolas; Ghenaim, Abdellah; Terfous, Abdelali
Abstract: This paper presents the implementation and validation of a strongly coupled numerical model of a fully passive flapping foil turbine operating at a high Reynolds number. Thanks to a strong fluid–solid coupling strategy, the well known added-mass instability is mitigated while simulating a lightweight flapping foil. The numerical results are first validated in the case of a fixed foil undergoing static stall. The model is then validated with respect to numerical results available in the literature for a heavy flapping foil turbine. Finally, the numerical results of the strongly coupled model are compared to experimental data of a lightweight turbine prototype tested in a confined channel. The numerical results have shown to be in good agreement with the experimental measurements. Indeed, the kinematics and harvesting performances of the turbine prototype have been accurately reproduced by the numerical simulations. Besides, the leading edge vortex shedding observed in the experiments has also been precisely reproduced by the numerical results. The strongly coupled model implemented and validated in the present paper constitutes a useful tool for expanding the parameter space in the search for an optimised design of the fully passive flapping foil turbine.